THE EFFECT OF CONTEXTUAL TEACHING AND LEARNING ON STUDENTS’ CONCEPTUAL UNDERSTANDING OF GEOMETRY - Saputra, Hery; Maulina, Suci; Mirunnisa, Mirunnisa; Razi, Zulfa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Mathematics becomes more meaningful when it is relevant to real life and students are more engaged in mathematics learning when it relates to them. Contextual teaching and learning (CTL) is a teaching concept that connects knowledge to real-world situations. The present study aims to investigate the effect of CTL on students’ conceptual understanding of geometry. This experimental study employed a pre-test-post-test control group design. The samples are all eighth-grade students in Junior High School 4, Sakti Pidie, A census sampling technique was used in this study since all members of the population served as samples. The experimental class and the control class were randomly selected from the two available classes. The experimental class was taught geometry using CTL while the control class was taught conventionally. Data were collected from pre-test and post-test that were declared valid. Data analysis was performed using the Kolmogorov-Smirnov test for normality test, the Levene test for homogeneity test, and t-test for the hypothesis testing. The results revealed that students taught using CTL have better conceptual understanding of geometry compared to those who were taught conventionally. It implies that the implementation of contextual teaching and learning (CTL) on geometry learning is effective to promote students’ learning.Keywords: Contextual teaching and learning, conceptual understanding, geometry learning.